A method for developing support networks for high-density Internet of Things through the integration of SDN and MEC technologies - Shefer, Oleksandr; Myhal, Stanislav (Національний технічний університет "Харківський політехнічний інститут", 2025)
The deployment of high- and ultra-high-density Internet of Things (IoT) systems poses a number of technical and organizational challenges. One promising approach to addressing these challenges is the integration of advanced network and data processing technologies, in particular Software-Defined Networking (SDN) and Multi-Access Edge Computing (MEC). This paper aims to explore the process of integrating SDN and MEC technologies into support infrastructures for high- and ultra-high-density IoT. Results. The study proposes an architecture for an integrated IoT–SDN–MEC system comprising both terrestrial and aerial segments. A mathematical model has been developed for this architecture, enabling the evaluation of energy consumption in fog-layer devices as well as the estimation of task execution delays. In addition, a traffic offloading scheme for the integrated IoT–MEC–SDN system is presented. The research formulates the problem of optimizing energy consumption and task processing delays in the aerial segment. To address this problem, the Grey Wolf Optimizer (GWO) algorithm is employed, providing efficient near-optimal solutions. Conclusion. Simulation results demonstrate that incorporating fog-layer resources within the aerial segment of the integrated IoT–MEC–SDN system significantly reduces both average energy consumption and average task processing delays in high- and ultra-high-density IoT environments. Future research will focus on determining the optimal structural configuration of the aerial segment.

При впровадженні ІоТ високої та надвисокої щільності виникає низка технічних та організаційних проблем. Одним з напрямів подолання цих проблем є інтеграція технологій опрацювання мереж та даних, зокрема SDN ТА MEC. Отже, метою даної статті є дослідження процесу інтеграції технологій SDN ТА MEC в системи підтримки високощільного та надвисокощільного Інтернету речей. Отримані результати. Запропонована архітектура інтегрованої системи ІоТ-SDN-МЕС, що складається з наземного та повітряного сегментів. Для даної архітектури розроблена математична модель, котра дозволяє визначати енергетичні витрати пристроїв туманного шару та часові затримки виконання завдань. Описана схема вивантаження трафіка в інтегрованій системі ІоТ-МЕС-SDN. Сформульовано завдання оптимізація енергоспоживання та затримок обробки завдань, вивантажених у повітряний сегмент. Для його вирішення застосований алгоритм зграї сірих вовків, який допомагає швидко знайти наближений розв’язок. Висновок. Проведений аналіз результатів моделювання функціонування інтегрованої системи ІоТ-МЕС-SDN показав, що при використанні у туманному шарі повітряного сегменту для високощільного та надвисокощільного Інтернету речей зменшуються середні енерговитрати та середня затримка, що виникає при обробці обчислювальних задач. Подальші дослідження у даному напрямі пов’язані з формуванням оптимальної структури повітряного сегменту.
Метод побудови мережі підтримки високощільного Інтернету речей з інтеграцією технологій SDN та MEC
Keywords: Internet of Things; Software-Defined Networking; Multi-Access Edge Computing; high-density; ultra-high-density; integrated system; terrestrial segment; aerial segment; Інтернет речей; технологія SDN; технологія MEC; високощільний; надвисокощільний; інтегрована система; наземний сегмент; повітряний сегмент